How Farmers Conceive and Cope with Megatrends: The Case of Finnish Dairy Farmers - Lahnamäki-Kivelä Susanna; Kuhmonen Tuomas (MDPI, 2022)
Megatrends (urbanization, digitalization, globalization, climate change, etc.) are mainstream developments that affect most economic activities. These megatrends have varying incidences and impacts on individual entrepreneurs and enterprises, also in farming sector. A farmer can either ignore or try to adapt to or benefit from megatrends. This reaction depends on many things: individuals' futures orientation, management practices, business strategy, sunk costs, the life cycle and type of business, for example. The study explores the association between eight common megatrends and business strategies among a sample of Finnish dairy producers. The analysis is based on survey data from the year 2019 (n = 135) collected among a major Finnish dairy industry co-operative's contract producers. The respondents evaluated the expected impact of the megatrends on their own business within the next 10 years with 5-point Likert-type scale (-2 horizontal ellipsis +2). K-means cluster analysis was utilized to uncover a few basic settings in the association between megatrends and farmers behaviours. After trying out several numbers of clusters, a distinctive three cluster solution was found. Additionally, cluster member profiles were framed with farmers' Likert -scale responses. The analysis indicates that dairy farmers differ in their observation of megatrends. The results confirm that some of the farmers more or less ignore the common megatrends, whereas some other farmers adapt to or benefit from the common megatrends. Supporting farmers' futures consciousness will strengthen their capacities of coping in the changing business environment.